A modernização da discriminação: transformações tecnológicas e desigualdades raciais no policiamento em São Paulo - Cedro, André Sales dos Santos (Universidade Federal de São Carlos, 2024)
Technology has modified and continues to modify social behavior, especially as a mediator of social relations. However, it is not only individuals who are subject to transformation. Institutions, including public and police entities, are also subject to changes in their course of action and relating – among themselves and with the population. The objective of this thesis is to analyze the impact of modernization and new technologies on the policing of the São Paulo State Military Police and how these changes perpetuate social and racial inequalities. The methodology used has qualitative character and includes field observation, ethnography, and interviews with military police officers. We conclude that technology aims to change the behaviors of security agents and the organizations they serve, establishing a new way of exercising crime control and police actions. However, by prioritizing reactive overt policing instead of community and preventive models, the São Paulo State Military Police contributes to the resurgence of practices linked to previous political periods and the militarized policing model, where discretionary and selective approaches are the main techniques employed.
The modernization of discrimination: technological transformations and racial inequalities in policing in São Paulo
Keywords: Tecnologia; Polícia Militar; Racismo Institucional; Controle do crime; Mídias digitais; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS